Status of Higher and Technical Education in Ladakh (Jammu & Kashmir, India) - Bupinder Zutshi; Rinchen Angmo (European Scientific Journal, ESJ, 2017)
Higher and technical education is critical to India’s aspirations of emerging as a major player in the global knowledge economy. Ladakh society for a long period experienced education given by monasteries, which at best provided basic education to the students. However, even this education was highly concentrated in Leh city and in a few monasteries. The conservative village people of Ladakh were somehow reluctant to send their children for formal education until 1981. Last decade 2001-2011 has significantly improved the literacy rates in Ladakh Division for both for both gender groups among rural and urban areas. Significant progress has been made to enroll students in the formal schools. However, net enrolment rates at middle, high and higher education levels are still, less as compared to Jammu & Kashmir overall average. The present paper examines the access, enrolments, infrastructure, quality challenges and opportunities for the higher and technical education system in Ladakh The study results depict strong need of improving higher and tertiary education in Ladakh with public-private partnership in order to have competitive edge for maintaining higher economic growth rates and improving Knowledge Development index in the region.